Leflunomide-induced interstitial lung disease (a systematic review) - Raj, Rishi; Nugent, Kenneth (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2013)
Background: Leflunomide, a disease modifying anti-rheumatic drug in use since 1998, causes interstitial lung disease (ILD) and other pulmonary complications. Methods: We undertook a systematic review of literature of PubMed (March 2013) to identify the published literature pertaining to pulmonary toxicity associated with leflunomide. Results: We identified 41 relevant articles detailing four population studies and case reports/series on an additional 42 patients. Available data were reviewed and summarized. Conclusions: Leflunomide can cause ILD. Most of these patients present within three months of starting leflunomide with acute symptoms for a week or less. Bilateral ground glass opacities and diffuse alveolar damage are the most common radiologic and histopathologic findings, respectively. Patients with pre-existing ILD are particularly at risk for this complication, and leflunomide should be avoided in this population. Activated charcoal and cholestyramine significantly decrease the half-life of the drug because of its enterohepatic circulation and should be considered in cases with acute toxicity.